2007
DOI: 10.1007/s11750-007-0035-y
|View full text |Cite
|
Sign up to set email alerts
|

Potential, value, and coalition formation

Abstract: Coalitional games, Value, Potential, Probabilistic models, 91A12,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
(49 reference statements)
0
6
0
Order By: Relevance
“…We thus depart from most of the previous literature in two respects: first, similar to Laruelle and Valenciano (2008a), we explicitly consider probabilistic games (N , v, P) where (N , v) is a standard TU game and P is a probability distribution on N 's power set 2 N . Second, we introduce a new value that reflects the difference between two conditional expectations.…”
Section: Unfortunately the Expectation E P I [V(s ∪ I) − V(s)]mentioning
confidence: 99%
See 1 more Smart Citation
“…We thus depart from most of the previous literature in two respects: first, similar to Laruelle and Valenciano (2008a), we explicitly consider probabilistic games (N , v, P) where (N , v) is a standard TU game and P is a probability distribution on N 's power set 2 N . Second, we introduce a new value that reflects the difference between two conditional expectations.…”
Section: Unfortunately the Expectation E P I [V(s ∪ I) − V(s)]mentioning
confidence: 99%
“…Knowing this might imply that j cannot (or must) be amongst the members of the coalition. This may have ramifications 9 Laruelle and Valenciano (2008a) refer to + i (N , v, P) as player i's "interim expected marginal contribution" and identify its relations with different classes of probabilistic values. 10 Note that the respective distributions P which need to be assumed in order to obtain the Shapley value as a conditional expected marginal contribution in (16) and (17) differ.…”
Section: The Prediction Valuementioning
confidence: 99%
“…A semivalue on G is a function that for each n restricts to a semivalue on X n . In [3] it was shown that in addition to the explicit form (5), the recursion…”
Section: Individual Measuresmentioning
confidence: 99%
“…Coalition formation. Consider the following model of coalition formation [5]. We assume that each possible coalition (subset S of X) forms with probability p(S), and that only one coalition S will form.…”
Section: Interpretation Of the Measuresmentioning
confidence: 99%
See 1 more Smart Citation